A thermoelectric copper-iodide composite from the pyrolysis of a well-defined coordination polymer. Issue 16 (9th April 2018) - Bai, Shi-Qiang; Wong, Ivy Hoi Ka; Lin, Ming; Young, David James; Hor, T. S. Andy
Abstract : A robust and relatively light CuI-rich carbon composite derived from an inorganic–organic hybrid molecular material demonstrates a high Seebeck coefficient from room temperature to 204 °C. Abstract : Coordination polymer1 was prepared from CuI and a flexible [SNS] ligand L in acetonitrile. The thermal decomposition of1 yielded a CuI-rich thermoelectric carbon composite2, which is relatively light, thermally stable and robust. Composite2 possesses high Seebeck coefficients (700–950 μV K −1 ) from rt to 204 °C after an optimization cycle.